Perubahan Beberapa Sifat Fisika-Mekanika Akibat Lintasan Pengolahan Tanah Dengan Traktor Poros-Dua Pada Beberapa Lahan Miring Dan Dampaknya Terhadap Hasil Kedelai - Yuswar Yunus (Universitas Syiah Kuala, 2010)
The research aimed to investigate how far increasing frequency of tractor traffic tillage on slopy ground could deteriorate land stability and soil productivity has been carried out by observing and analyzing the changes of soil physical-mechanical properties underneath wheel tracks of a 2-WD tractor, at Andisols Order Soil. The experiment was conducted at the experimental field of Sare, gampoeng Aceh Village, Sub-province Aceh Besar, Aceh Province, from April up to September 2009. The altitude is 445 m above sea level. Research method employed, encompassing: (1) variance analysis due to factorial split-plot random design, to observe the effect of the treatments on soil productivity as indicated by soybean plant (Gycin max L.). The design consisted of three levels of treatments of land slope as the main plots, where: k1 = 0 -5 percent (relatively flat), k2 = 6 -10 percent (rather slopy), dan k3 = 11-15 percent (slopy/critical), and six levels of treatments of traffic tillage frequency as split plots, where: l0 = no traffic, l1 = one time traffic, l2 = three times traffic, l3 = five times traffic, l4 = seven times traffic, and l5 = nine times traffic, each at two replications, respectively; and (2) regression and correlation analysis that was used to observe the relation of traffic tillage frequency and changes of soil physical-mechanical properties as indications of land stability and productivity changes. Data observed were: soil bulk density, total porosity, stability index of soil aggregates, soil permeability, moisture content, soil consistency, soil plasticity, soil cne index, soil shear strength, and land productivity indicated by yield components of soybean plant, i.e.; root length, root weight, and yield of soybean plant. Results of the research generally indicated that maximum percentage of soil physical-mechanical changes occurred in k1 to k3 at l2 was tolerable for its soil stability index was greater than 30 in which the yield of soybean – relatively low though, varied at the local level within 0.6-1.9 tonnes a hectare. Obtained from variance analysis the yield of soybean interacted significantly at l0-l5 as well as at k1-k3. Quantitatively, the results showed that the changes of soil physical-mechanical properties as well as growth components and yield of soybean were significantly different at increasing frequency of tillage traffic and land slopes. While qualitatively, obtained from regression-correlation analysis the above indication showed polynomial relations of a reliability R2 of 0.96 to 1.00 for yield of soybean plant and stability index of soil aggregates at increasing frequency of traffic tillage of l0-l5 in the three land slopes of k1-k3..